Cyclic di-AMP alleviates periodontitis by activating PI3K/Akt/Nrf2 pathways - Luo, Kaihua; Wu, Qinrui; Li, Zhengyi; Wu, Yajie; Su, Zhifei; Zhou, Fangjie; Li, Qinyang; Ren, Biao; Li, Yuqing; Li, Jiyao; Peng, Xian (Frontiers in Cellular and Infection Microbiology, 2025)
Emerging research demonstrates the regulatory effects of c-di-AMP, a bacterial-derived small molecule secondary messenger, on host immune responses and promoting resistance against infection-related diseases. This study aims to elucidate the role of c-di-AMP in the occurrence and development of periodontitis. Using model of ligation-induced periodontitis, we observed that c-di-AMP effectively alleviated alveolar bone resorption. Transcriptomic sequencing in mice gingival tissues demonstrated that treatment with c-di-AMP led to a significant upregulation of the PI3K/Akt signaling pathway and its key components, including Akt3. Concurrently, we observed an upregulation of the cGMP/PKG signaling pathway. To validate our findings, we treated gingival epithelial cells with c-di-AMP and confirmed the activation of the PI3K/Akt pathway by c-di-AMP in gingival epithelial cells. Under LPS-induced inflammation, c-di-AMP significantly suppressed the release of inflammatory factors (such as IL-6 and TNF-α) from gingival epithelial cells. Moreover, key components of the PI3K/Akt pathway, including Akt, and downstream inflammation regulatory gene Nrf2, were upregulated, which were also confirmed at the protein level. Collectively, this study demonstrates that c-di-AMP definitely plays a role in alleviating periodontitis. Our findings highlight the mechanisms by which c-di-AMP modulates periodontitis, including activating the PI3K/Akt pathway and potentially involving the cGMP/PKG pathway, ultimately contributing to improved immune defense and maintenance of bone homeostasis.